EFL Students' Writing Self-Efficacy and Writing Performance in a Senior High School: A Correlational Study - Maya Tri Astuti; Astri Hapsari (Universitas Muria Kudus, 2026)
Although writing self-efficacy is essential for the development of second/foreign language learners' writing skills, there are still limited studies on EFL writing self-efficacy among senior high school students in the Indonesian context. This study aims to test the correlation between students' EFL writing self-efficacy and their performance in writing a procedural text in a senior high school.One hundred and sixty-three students agreed to participate in the study. The researcher used an Indonesian version of the Second Language Writing Self-Efficacy Scales by Teng et al. (2017). The result showed a significantly negative correlation (r = -.089) between students' self-confidence in writing and their actual writing performance, with a significance ρ value = .257, in which it is greater than the significance level of Cronbach's alpha (Î± = 0.05). Therefore, the null hypothesis (H0) is accepted that there is no significant correlation between writing self-efficacy and writing performance. As it is limited to students from one school in grade 11 and procedural text, future research needs to be conducted with more participants and diverse text types to enrich the discussion and explore factors that contribute more substantially to these text types.